Thermal Expansion Reduction in Alumina‐Toughened Zirconia by Incorporation of Zirconium Tungstate and Aluminum Tungstate. Issue 9 (20th June 2015) - Romao, Carl P.; Marinkovic, Bojan A.; Werner‐Zwanziger, Ulrike; White, Mary Anne; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> A series of composites containing yttria‐stabilized zirconia, Al2O3, and the thermomiotic (negative thermal expansion) materials ZrW2O8 and Al2W3O12 were prepared by an in situ solid‐state reaction during sintering. Microstructural analysis of the composites indicated several sub‐micron sized components. 27Al MAS NMR was used to characterize the aluminum‐containing phase distribution. Measurement of the coefficients of thermal expansion showed that the addition of thermomiotic components reduced the thermal expansivity of the alumina‐toughened zirconia matrix, but the reduction was considerably smaller than what would be predicted by the rule of mixtures. The Turner model was much more accurate in predicting the coefficients of thermal expansion of the composites due to the large differences in stiffness between the components.